Surgical anatomy of the renal transplant: Exemplifying the incorporation of anatomy in non-medical sciences - Redondo-Sáenz, Diego (2021)
Anatomy is of vital importance in health sciences. Although its centrality is demonstrated in disciplines such as Medicine, in others such as Nursing it remains doubtful as its importance tries to be explained through subjects of interest aside from the correspondent disciplinary focus. The current bibliographic review aims to exemplify the importance of this discipline in Nursing by describing the surgical anatomy of renal transplant and its relationship with the most prevalent nursing diagnoses in this period. The problem-based learning methodology allowed to understand the updates in the anatomical bases of renal transplant’s surgical technique and its influence in the nursing diagnoses present before, during, and after surgery. It is concluded that anatomy constitutes a science of vital importance for the education and practice of all health sciences, while it exists a bidirectional feedback between morphological sciences and Nursing.